A Causal Model of BIM Adoption in the Thai Architectural and Engineering Design Industry. (2017) - Ngowtanasawan, Grit
Abstract: Building Information Modeling (BIM) is a computer technology for design and management of buildings and facilities, which is widely adopted for implementing design projects in many countries. Thailand is one of those countries which has adopted the changing design technology of BIM to use in the Thai architectural and engineering design industry. The purpose of this research was to develop a causal model of the factors influencing BIM adoption behaviors in the Thai architectural and engineering design industry. The related theories and research papers were thoroughly explored and examined in order to find out the related factors. The initial factors were confirmed and validated by a group of experts. The final factors were used to formulate a structural equation model (SEM) for studying the relationship among the factors. The empirical data was collected from a group of Thai engineers and architects with experiences in using BIM (278 respondents). The results suggested that the factor that had a positive significant influence on BIM adoption was BIM characteristics. The indicators of the BIM characteristics comprised the following: (1) quality of the product, (2) relative advantage, (3) trialability, (4) ease of use, and (5) compatibility. The strategies for the adaptation of the Thai architectural and engineering design industry to the BIM adoption were also discussed in the conclusion of this article.